An all-solid-state thin-layer laminated cell for calibration-free coulometric determination of K+. (10th March 2022) - Tatsumi, Shiho; Omatsu, Terumasa; Maeda, Kohji; Mousavi, Maral P.S.; Whitesides, George M.; Yoshida, Yumi
Highlights: An all-solid-state thin-layer laminated cell realized calibration-free coulometric determination of K + ions. The cell achieved complete mass transport of the target ion from a 1 mm 3 drop of the aqueous sample. An originally prepared conducting-polymer-dispersed ink was cast on the carbon electrode. The cell allows the calibration-free determination of K + ions in a 1 mm 3 drop of ten-fold-diluted serum. Abstract: Calibration-free coulometric determination of K + ions was realized using an all-solid-state thin-layer laminated cell with a simple laminate structure. The fabricated cell consists of a Ag/AgCl electrode, a plastic spacer for positioning the aqueous sample solution, an organic ion-selective membrane, and a conducting polymer/carbon electrode. An originally prepared conducting-polymer-dispersed ink was cast on a conductive carbon sheet (a screen-printed graphite electrode or carbon paper) to fabricate the conducting polymer/carbon electrode. The cell achieved complete mass transport of the target ion from a 1 mm 3 drop of the aqueous sample to the organic ion-selective membrane under a constant potential between the Ag/AgCl electrode and the conducting polymer/carbon electrode, which generated electrical current for enabling the ion transfer. The electric charge obtained by integrating the electric current was used to estimate the molar amount of the target ion in the sample drop. For tetraethylammonium cations (TEA + ; 20–200 μmol dm −3 ), the evaluated molar amounts corresponded to 92%–94% of the initial mole amounts. The repeatability estimated using the same cell was ±4%–6%, and the device-to-device reproducibility was ±4% for five cells. In terms of K + -ion detection (0.1–0.8 mmol dm −3 ) in sample drops containing NaCl (14 mmol dm −3 ), the evaluated molar amounts corresponded to 86%–92% of the initial molar amounts, indicating the promise of the all-solid-state thin-layer laminated cell for achieving the calibration-free determination of K + ions in a 1 mm 3 drop of ten-fold-diluted serum. Graphical abstract: Image, graphical abstract